Climate change and individual behavior - René Bernard; Panagiota Tzamourani; Michael Weber (ZBW - Leibniz Information Centre for Economics, 2022)
This paper studies the causal effect of providing information about climate change on individuals' willingness to pay to offset carbon emissions in a randomized control trial. Receiving truthful information about ways to reduce CO2 emissions increases individuals' willingness to pay for CO2 offsetting relative to the control group. Individuals receiving information about the behavior of peers react similarly to those receiving information about scientific research. Indi-viduals' responses vary depending on their socio-demographic characteristics and also along a rich set of prior beliefs and concerns regarding climate change. In a follow-up survey, we study the endogenous information acquisition of survey participants and show that individuals choose information that aligns with their views. Individuals who choose to receive information about climate change have a higher willingness to pay for CO2 offsets.
Keywords: D10; D83; D91; Q54; 330; Climate change; information treatment; willingness to pay; CO2 compensation; information acquisition